PERANAN K. H. HASYIM ARSYAD SEBAGAI TOKOH PENYEBAR AGAMA ISLAM DI KOTA PEKANBARU TAHUN 1950-2000 - Ilham Alfads; Isjoni Isjoni; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Islamic religion entered Indonesia is a proscess in the history of Indonesia. The process of entering the religion of Islam into Riau was brought by traders from Arabian, Persia, and Gujarat who had the aim to trade and thus spread the religion of Islam. The purpose of this study was to determine the life history of K. H. Hasyim Arsyad, and to know the constraints faced by K. H. Hasyim Arsyad. The benefits of this research are adding and increasing the ability of researchers to write scientific papers, expanding for writers in writing scietific papers, expanding for writers in writing scientific papers. In this study using qualitative methods. Qualitative method is a methodthat does not use steps in data collection and in providing interpretation of the result. The result of this study are K. H. Hasyim Arsyad was a prominent figure and ulam in Pekanbaru, duruing the range of the 1950-2000 he preached in Pekanbaru in the spread of Islam and benefited the community. He always gives advice to the community in dealing with any problems.Key Words: K. H. Hasyim Arsyad, Propagators of Islam, Role